S-Glutathionylation of Protein Disulfide Isomerase Regulates Estrogen Receptor α Stability and Function - Ying Xiong; Yefim Manevich; Kenneth D. Tew; Danyelle M. Townsend (International Journal of Cell Biology)
S-Glutathionylation of cysteine residues within target proteins is a posttranslational modification that alters structure and function. We have shown that S-glutathionylation of protein disulfide isomerase (PDI) disrupts protein folding and leads to the activation of the unfolded protein response (UPR). PDI is a molecular chaperone for estrogen receptor alpha (ERα). Our present data show in breast cancer cells that S-glutathionylation of PDI interferes with its chaperone activity and abolishes its capacity to form a complex with ERα. Such drug treatment also reverses estradiol-induced upregulation of c-Myc, cyclinD1, and P21Cip, gene products involved in cell proliferation. Expression of an S-glutathionylation refractory PDI mutant diminishes the toxic effects of PABA/NO. Thus, redox regulation of PDI causes its S-glutathionylation, thereby mediating cell death through activation of the UPR and abrogation of ERα stability and signaling.